Method for improving texture uniformity of superfine electronic wire

Through the processing of turning, alkaline washing, and continuous squeezing, the problems of uneven distribution and high H content of aluminum alloy electronic lines were solved, and the tissue uniformity, conductivity and extension rate of electronic lines were improved. Silk rate.

CN119351906APending Publication Date: 2025-01-24INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202310860029.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

During the production process, existing aluminum alloy electronic wires have problems such as uneven distribution of primary phases and excessive H content, resulting in poor tissue uniformity, low conductivity and high wire breakage.

Method used

Through the surface of the aluminum alloy ingot, alkaline washing and continuous squeezing treatment are performed, the H content is reduced and the iron is crushed to make it evenly distributed.

Benefits of technology

It improves the electrical conductivity and elongation of aluminum alloy, reduces the wire breakage rate and the scattering effect of H, and enhances the uniformity and production efficiency of the alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351906A_ABST
    Figure CN119351906A_ABST
Patent Text Reader

Abstract

The invention relates to the field of aluminum alloy production, in particular to a method for improving the structure uniformity of a superfine electronic wire. The applicable alloy components of the invention are as follows: 0.30-0.80 wt.% of Fe, less than or equal to 0.30 wt.% of Cu, less than or equal to 0.05 wt.% of Mg, less than or equal to 0.10 wt.% of Si, less than or equal to 0.05 wt.% of Zn, less than or equal to 0.04 wt.% of B, less than or equal to 0.10 wt.% of rare earth and the balance of Al. The preparation method of the superfine electronic wire comprises the following steps: (1) ingot casting and skin turning; (2) conventionally extruding the cast ingot; (3) carrying out alkali washing and blow-drying on the blank rod; (4) continuously extruding the blank rod; and (5) wire drawing. The preparation process is simple, second-phase particles in the prepared alloy are fine and dispersed, the structure uniformity is high, the wire breaking rate in the wire drawing process is low, and the production efficiency is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of aluminum alloy production, and in particular to a method for improving the uniformity of ultrafine electronic wire structure. Background Art

[0002] The demand for lightweight equipment in new energy vehicles, rail transit, aerospace, etc. has gradually increased. For example, as an indispensable component of new energy vehicles, the total weight of the wiring harness in the car continues to increase with the improvement of the degree of intelligence. According to statistics, the weight of the wiring harness in new energy vehicles accounts for about 5% of the weight of the whole vehicle. As the most important component of the wiring harness, electronic wire, its selection and development play a vital role in the lightweight of the wiring harness. Compared with copper alloy, the density of aluminum is less than 1 / 3 of it, and the price is less than 1 / 3 of copper. Therefore, the use of aluminum alloy electronic wire to replace the existing copper alloy electronic wire is increasingly valued by OEMs.

[0003] The production process of aluminum alloy wire harness can be roughly divided into the production of ingots and electrical round rods, drawing into wires, heat treatment and twisting into wires. Among them, Al-Fe alloys will form a mesh-like iron-rich primary phase distributed along the grain boundaries during the casting process. The existence of this type of primary phase will have a significant effect on the electrical conductivity and mechanical properties of the alloy. Therefore, it is usually necessary to break this type of primary phase in the subsequent processing process and disperse it in the electronic wire. In addition, H will inevitably be introduced into the alloy during the production process. The increase in H content will not only increase the scattering effect on electrons, but also reduce the uniform plastic deformation ability of the alloy by promoting strain localization. For ultrafine electronic wires (diameter <0.3mm), the uniformity of its structure will not only determine whether it can be drawn into a filament of the required diameter by affecting the wire breakage during the drawing process, but also affect the final product performance of the electronic wire. Therefore, it is very necessary to design a processing technology to improve the uniformity of the structure of ultrafine electronic wires. Summary of the invention

[0004] The object of the present invention is to provide a method for improving the uniformity of the structure of ultrafine electronic wires. By adopting appropriate processing technology, the crushing effect of the iron-rich phase is improved as much as possible so that it is evenly distributed in the matrix, and at the same time, the H content in the alloy is reduced to improve the yield rate in the alloy drawing process, thereby improving the final conductivity and elongation of the ultrafine electronic wires.

[0005] In order to achieve the above object, the technical solution of the present invention is:

[0006] A method for improving the uniformity of ultrafine electronic wire structure, comprising the following process steps:

[0007] 1) Turning the surface of the aluminum alloy ingot to eliminate pores and inclusion defects on the surface of the aluminum alloy ingot;

[0008] 2) heating the aluminum alloy ingot to an extrusion temperature of 320° C. to 400° C., holding the ingot at this temperature for 1 to 5 hours, and hot-extruding the aluminum alloy ingot into a round billet rod using a horizontal extruder;

[0009] 3) putting the round billet into an alkali washing tank for alkali washing, followed by washing and drying;

[0010] 4) Extruding the alkali-washed round billet rod continuously for 2 to 8 times, with the continuous extruder rotating at a speed of 4 to 12 rpm, followed by annealing at 360 to 520° C. for 2 to 5 hours;

[0011] 5) The aluminum alloy rod obtained in step 4) is drawn to The alloy single wire is placed in an annealing furnace and kept at 160-300°C for 1-6 hours.

[0012] In the method for improving the uniformity of the structure of ultrafine electronic wires, in step 1), the aluminum alloy ingot is turned to a thickness of not less than 3 mm.

[0013] In the method for improving the uniformity of the structure of ultrafine electronic wires, in step 2), the extrusion temperature is 340° C. to 380° C., and the heat preservation time is 1.5 to 3 hours.

[0014] In the method for improving the uniformity of the structure of ultrafine electronic wires, in step 3), the alkali washing time is not less than 10 minutes, and after the alkali washing, the residual alkali solution on the round blank rod is cleaned and blown dry.

[0015] In the method for improving the uniformity of the structure of ultrafine electronic wires, in step 4), the continuous extrusion passes are 4 to 6 passes, the extruder speed is 4 to 10 rpm, the annealing temperature is 400° C. to 460° C., and the annealing time is 3 to 4 hours.

[0016] In the method for improving the uniformity of the structure of ultrafine electronic wires, in step 5), the annealing temperature of the alloy single wire is 200-280° C., and the annealing time is 2-5 hours.

[0017] The method for improving the uniformity of the structure of ultrafine electronic wires, the chemical composition of the ultrafine electronic wires is: Fe content is 0.30-0.80wt.%, Cu content is ≤0.30wt.%, Mg content is ≤0.05wt.%, Si content is ≤0.10wt.%, Zn content is ≤0.05wt.%, B content is ≤0.04wt.%, rare earth content is ≤0.10wt.%, and the balance is Al.

[0018] The method for improving the uniformity of the structure of ultra-fine electronic wires, the alloy monofilament is used for wiring harnesses or cables in new energy vehicles, rail transportation and aerospace carriers.

[0019] The design concept of the present invention is:

[0020] The present invention requires turning the surface of the aluminum alloy ingot, which can effectively reduce defects such as pores and inclusions in the alloy and prevent them from entering the aluminum alloy round billet rod during the extrusion process; alkali washing, cleaning and drying the billet rod before continuous extrusion can also reduce the possibility of oil and water vapor being involved in the aluminum alloy round billet rod. The above treatment can effectively reduce the H content in the aluminum alloy round billet rod, reduce the scattering effect of H on electrons in the alloy, and improve the electrical conductivity of the alloy. At the same time, the reduction in H content can reduce the strain localization caused by the alloy in the subsequent plastic deformation process, improve the uniformity of the alloy, and then reduce the wire breakage rate of the aluminum alloy round billet rod during the drawing process. In addition, the above treatment can also avoid the blistering phenomenon of the round billet rod or the alloy wire in the subsequent annealing process, and improve the yield rate in the alloy production process.

[0021] The preferred continuous extrusion passes of the present invention are 4 to 6 times. Through multiple continuous extrusion passes, the primary Fe-rich phase can be further broken, the size of the second phase particles can be reduced, and the uniformity of the second phase particle distribution can be improved. In addition, the continuous extruder speed of 4 to 10 rpm is preferred. On the one hand, it can ensure the production efficiency of the aluminum alloy round billet rod; on the other hand, it can avoid the temperature rise caused by the faster speed and reduce the occurrence of dynamic recrystallization. While reducing dynamic recrystallization, the crushing effect of the plastic metal flow on the second phase particles can be further enhanced, and the particles can be more evenly dispersed in the matrix, thereby improving the uniform deformation ability of the alloy during the drawing process and improving the conductivity and elongation of the ultrafine electronic wire.

[0022] The advantages and beneficial effects of the present invention are:

[0023] The preparation process of the invention is simple, the second phase particles in the prepared alloy are fine and dispersed, the organization is highly uniform, the wire breakage rate is low during the wire drawing process, and the production efficiency is high. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the EPMA surface scan of the Fe element of the aluminum alloy billet rod prepared in Example 1.

[0025] Figure 2 This is the EPMA surface scan of the Fe element of the aluminum alloy billet rod prepared in Comparative Example 1. DETAILED DESCRIPTION

[0026] In the specific implementation process, the present invention proposes a method for improving the uniformity of ultrafine electronic wire structure, and the method process is as follows: ingot car → conventional ingot extrusion → billet rod alkali washing and drying → billet rod continuous extrusion → wire drawing.

[0027] The process is further described below in conjunction with examples of implementation, but the present invention is not limited to these examples.

[0028] Example 1

[0029] In this embodiment, a method for improving the uniformity of ultrafine electron wire structure includes the following steps:

[0030] 1) The alloy raw materials are melted in a resistance furnace, and the designed Al-Fe alloy composition is: 0.59% iron and the balance aluminum, in terms of element mass percentage.

[0031] The smelting process is as follows: first, industrial pure aluminum with a purity of 99.9wt% and Al-Fe master alloy are put into a resistance furnace and heated to 830°C. After they are fully melted, the temperature is lowered to 740°C. After being kept warm for 10 minutes, degassing treatment is performed, and then the temperature is lowered to 720°C for casting. The obtained Al-Fe alloy ingot is air-cooled to room temperature.

[0032] 2) The prepared Al-Fe alloy ingot is heated to 470°C in a box-type resistance furnace, kept warm for 24 hours, and air-cooled to room temperature. Then, a layer of turning is performed on the surface of the Al-Fe alloy ingot, and the turning thickness is 3 mm to eliminate defects such as pores and inclusions on the surface of the Al-Fe alloy ingot as much as possible.

[0033] 3) The Al-Fe alloy ingot is kept at 380℃ for 2h and then hot extruded into The billet rod has an extrusion die temperature of 400-420°C, an extrusion rod displacement speed of 7.2 mm / s, an extrusion ratio of about 169:1, and is then air-cooled to room temperature.

[0034] 4) Place the blank rod into the alkali washing tank for alkali washing for no less than 10 minutes, then clean and blow dry.

[0035] 5) The alkali-washed billet rod was continuously extruded for 4 times at a speed of 6 rpm, and then annealed at 420°C for 3h and air-cooled to room temperature to obtain Aluminum alloy rod;

[0036] 6) The aluminum alloy rod obtained in step 5) is drawn to The alloy single wire is placed in an annealing furnace, kept at 220°C for 4 hours, and air-cooled to room temperature.

[0037] The technical indicators of this embodiment are as follows: During the wire drawing process, 30,000 meters of wire can be drawn continuously without breaking. The conductivity of the ultra-fine electronic wire prepared by this embodiment is ≥62.3% IACS, the tensile strength of the alloy is ≥120MPa, and the elongation after fracture is

[0038] ≥15%.

[0039] Example 2

[0040] The difference from Example 1 is that:

[0041] 1) The designed Al-Fe alloy composition is, by element mass percentage, iron: 0.51%, copper: 0.20%, magnesium: 0.02%, boron: 0.02%, and the balance is aluminum.

[0042] 2) The alkali-washed billet rod was continuously extruded for 6 times at a speed of 4 rpm, and then annealed at 420°C for 3h and air-cooled to room temperature to obtain Aluminum alloy rod;

[0043] The technical indicators of this embodiment are as follows: During the wire drawing process, the alloy can be continuously drawn for 30,000 meters without breaking. The conductivity of the ultra-fine electronic wire prepared by this embodiment is ≥62.1% IACS, the tensile strength of the alloy is ≥125MPa, and the elongation after break is ≥13%.

[0044] Example 3

[0045] The difference from Example 1 is that:

[0046] 1) The aluminum alloy rod after alkali washing, cleaning and drying is continuously extruded for 5 times;

[0047] 2) Select a continuous extrusion speed of 1 to 11 rpm, then anneal at 380°C for 4 hours, and air cool to room temperature to obtain Aluminum alloy rod.

[0048] As shown in Table 1, the results of the effect of the continuous extrusion speed on the alloy structure and properties in this embodiment. It can be seen from Table 1 that the alloy recrystallization fraction gradually increases with the increase of the continuous extrusion speed. When the continuous extrusion speed is 3 to 7 rpm, the second phase crushing effect is the best, and the alloy can obtain a conductivity higher than 62% IACS after annealing.

[0049] Table 1

[0050]

[0051] Comparative Example 1

[0052] The difference from Example 1 is that:

[0053] 1) The designed Al-Fe alloy composition is, by element mass percentage, iron: 0.51%, lanthanum: 0.079%, and the balance is aluminum.

[0054] 2) The aluminum alloy rod after alkali washing, cleaning and drying is subjected to only one continuous extrusion process, with the continuous extruder speed being 6 rpm, followed by annealing at 420° C. for 3 h and air cooling to room temperature.

[0055] The technical indicators of this comparative example are as follows: During the wire drawing process, wire breakage often occurs. The conductivity of the ultrafine electronic wire prepared by this comparative example is 61.8% IACS, the tensile strength of the alloy is 121 MPa, and the elongation after break is 13%.

[0056] like Figure 1 and Figure 2 As shown, the EPMA surface scan results of Fe element of the alloy billet prepared in the above Example 1 and Comparative Example 1. It can be seen from the figure that the use of the present invention can significantly reduce the size of the second phase particles, making their distribution more uniform and dispersed, thereby significantly improving the uniformity of the alloy structure.

[0057] The results of the embodiments and comparative examples show that by adopting the process method and flow of the present invention, the uniformity of the alloy structure is significantly improved, the uniform plastic deformation ability of the alloy is improved, and the comprehensive performance of the ultra-fine electronic wire is greatly improved. At the same time, due to the reduction of the wire breakage rate, the production efficiency and yield rate in the production process of ultra-fine electronic wire are significantly improved, and its performance indicators are as follows: the conductivity range is 62.0% IACS to 63.0% IACS, the tensile strength of the alloy is ≥120MPa, and the elongation after break is 13% to 20%.

Claims

1. A method for improving the uniformity of ultrafine electron wire structure, characterized in that: The process steps include: 1) Turning the surface of the aluminum alloy ingot to eliminate pores and inclusion defects on the surface of the aluminum alloy ingot; 2) heating the aluminum alloy ingot to an extrusion temperature of 320° C. to 400° C., holding the ingot at this temperature for 1 to 5 hours, and hot-extruding the aluminum alloy ingot into a round billet rod using a horizontal extruder; 3) putting the round billet into an alkali washing tank for alkali washing, followed by washing and drying; 4) Extruding the alkali-washed round billet rod continuously for 2 to 8 times, with the continuous extruder rotating at a speed of 4 to 12 rpm, followed by annealing at 360 to 520° C. for 2 to 5 hours; 5) The aluminum alloy rod obtained in step 4) is drawn into alloy single wires with a diameter of 0.2 to 0.32 mm, and the obtained alloy single wires are placed in an annealing furnace and kept at 160 to 300° C. for 1 to 6 hours.

2. The method for improving the uniformity of ultrafine electron wire structure according to claim 1, characterized in that: In step 1), the turning thickness of the aluminum alloy ingot is not less than 3 mm.

3. The method for improving the uniformity of ultrafine electron wire structure according to claim 1, characterized in that: In step 2), the extrusion temperature is 340° C. to 380° C., and the holding time is 1.5 to 3 hours.

4. The method for improving the uniformity of ultrafine electron wire structure according to claim 1, characterized in that: In step 3), the alkali washing time is not less than 10 minutes. After the alkali washing, the residual alkali solution on the round billet rod is cleaned and blown dry.

5. The method for improving the uniformity of ultrafine electron wire structure according to claim 1, characterized in that: In step 4), the continuous extrusion passes are 4 to 6 passes, the extruder speed is 4 to 10 rpm; the annealing temperature is 400° C. to 460° C., and the annealing time is 3 to 4 hours.

6. The method for improving the uniformity of ultrafine electron wire structure according to claim 1, characterized in that: In step 5), the alloy single wire annealing temperature is 200-280° C., and the annealing time is 2-5 hours.

7. The method for improving the uniformity of ultrafine electron wire structure according to claim 1, characterized in that: The chemical composition of the ultrafine electronic wire is as follows: Fe content is 0.30-0.80wt.%, Cu content is ≤0.30wt.%, Mg content is ≤0.05wt.%, Si content is ≤0.10wt.%, Zn content is ≤0.05wt.%, B content is ≤0.04wt.%, rare earth content is ≤0.10wt.%, and the balance is Al.

8. The method for improving the uniformity of ultrafine electron wire structure according to claim 1, characterized in that: Alloy monofilaments are used in wiring harnesses or cables in new energy vehicles, rail transit and aerospace carriers.

Citation Information

Cited By

  • Aluminum filament and preparation method and application thereof

    CN122256769A

  • Aluminum filaments, methods of making and using the same

    CN122256769B